Capacity improved robust lossless image watermarking. Issue 11 (1st November 2014) - Thabit, Rasha; Khoo, Bee Ee
Abstract : Nowadays, the lossless watermarking methods that can resist attacks have attracted more attention. Obtaining a robust lossless watermarking was at the cost of reducing the capacity and the watermarked image quality. This study presents a new robust lossless watermarking scheme in the transform domain where the Slantlet transform (SLT) has been applied to transform the host image and blocks of the SLT coefficients have been selected for the embedding process. The histograms of the selected blocks are modified according to a predefined threshold value to carry the watermark bits. The overflow/underflow of the pixel values have been avoided by using a pixel adjustment method as a post‐processing step. In the proposed scheme, the original host image can be recovered without any distortion after the hidden watermark has been extracted and the watermark can withstand different kinds of attacks. In comparison with the previous methods, the proposed scheme has higher embedding capacity, better robustness against unintentional attacks and improved visual quality. The results of the experiments prove the efficiency of the proposed scheme.